Filosofía de lo bello en Kant - Peñuela, Jorge Edilberto (Revista Científica, 2006)
Kant provides to modernity their theoretical foundations and became one of the most prominent thinkers of century XVIII, His ideas have extended all over the European culture, in such a way that its legacy exerted influence in all those that hadlive in the acces to their conceptual universe and in all we who live in the contemporary world. In this essay I analyze concepts of the philosophy of the art of Kant, in special its reflection on beauty and on pleasure. The activity of our cognitive faculties is stimulated for the formulation of a judment, once we have experienced the presence of beauty, in the nature or in the art. Beauty has stopped being a Methaphysical concept and it has become the registry of an activity of the human understanding that, by means of taste judgments, models a community feeling. In his opinion, thanks to the exercise of reason, the task of the philosopher is essentially in observing, experiencing and to describe those called aesthetic phenomena, using as methodology the technique of the experience, valuing sensitivity,the common sense, the imagination, the memory, the feeling and the operability of the reason. Kant decides to confront the challenge to review the conceptual tradition meticulously that gives account of the artistic experience,-analyzes the intellectual faculties that take part in the conformation of the taste like origin of the experience of the art; he explains pleasure and pain that stimulated in the spectator.